(untitled) (Revista Innova Educación, 2021)
The objective was to establish imaginative education in analytical skills in the history subject at the Veintitrés de Octubre Educational Unit of the Montecristi canton, Manabí province, Ecuador. To achieve this purpose, a mixed methodological approach was applied. First, the exploratory research allowed the application of surveys to teachers and students for data collection. Among the main findings found, the deficient application of imaginative education in history classes was evidenced due to the limited knowledge of this methodology on the part of teachers. 43% of the teachers surveyed know little or nothing about the tools of imaginative education, and a considerable 30% realize it moderately. For these and more reasons it is concluded that it is suitable as a strategy for teaching the subject above.